Answer:
y=1
Step-by-step explanation:
Step 1: Simplify both sides of the equation.
6=2(y+2)
6=(2)(y)+(2)(2)(Distribute)
6=2y+4
Step 2: Flip the equation.
2y+4=6
Step 3: Subtract 4 from both sides.
2y+4−4=6−4
2y=2
Step 4: Divide both sides by 2.
2y/2 2/2
Answer: Second Option
Step-by-step explanation:
We have the following expression:
We have the following expression:
To solve the expression, apply the inverse of on both sides of the equality.
Remember that:
So we have to:
The answer is the second option
Working out will help too, thanks:)